Arcobacter butzleri: Underestimated Enteropathogen - Prouzet-Mauléon, Valérie (Centers for Disease Control and Prevention, 2006)
Molecular methods applied to 2,855 strains of Campylobacter-like organisms received from a surveillance network of Campylobacter infections in France identified 29 Arcobacter butzleri infections. This species ranks fourth for Campylobacteraceae isolation and appears to have the same pathogenic potential as the other species in the genus.